Textual variation and version control in the TEI. - Smith, David (Computers & the Humanities, 1999)
Discusses variation and version control outlined in the Text Encoding Initiative's (TEI) Guidelines for Electronic Text Encoding and Interchange. Problems that require more than the standard TEI textual critical elements; Solutions to the problem of transposition, variation of meta-data and insertion of incomplete structures.